“Happy” in Za’atari: Difference and Global Belonging in the Refugee Camp Imaginary (2022)
This article analyzes two video remakes of Pharrell Williams’s hit song “Happy” portraying Za’atari refugee children. I discuss the role that the “Happy” tribute video trend had in developing a global imaginary that lends itself to current conversations around humanitarian happiness and “deexceptionalizing” migration and humanitarian space. I look at the videos in relationship to this trend and to the media construction of Za’atari camp as “city.” In the context of this debate and reading the videos through the paradigm of global urbanness such as we also see in the “Happy” craze, I argue that in fact the videos show the limits of the ideology of global belonging when it comes to the refugee camp and of the incommensurability of contemporary humanitarian and global imaginaries, even in an age defined by the sway of new media.